Relationships of tree height and diameter at breast height revisited: analyses of stem growth using 20-year data of an even-aged Chamaecyparis obtusa stand - Sumida, Akihiro (Oxford University Press, 2013)
Stem diameter at breast height (DBH) and tree height (H) are commonly used measures of tree growth. We examined patterns of height growth and diameter growth along a stem using a 20-year record of an even-aged hinoki cypress (Chamaecyparis obtusa (Siebold & Zucc.) Endl.) stand. In the region of the stem below the crown (except for the butt swell), diameter growth rates (ΔD) at different heights tended to increase slightly from breast height upwards. This increasing trend was pronounced in suppressed trees, but not as much as the variation in ΔD among individual trees. Hence, ΔD below the crown can be regarded as generally being represented by the DBH growth rate (ΔDBH) of a tree. Accordingly, the growth rate of the stem cross-sectional area increased along the stem upwards in suppressed trees, but decreased in dominant trees. The stem diameter just below the crown base (D(CB)), the square of which is an index of the amount of leaves on a tree, was an important factor affecting ΔDBH. D(CB) also had a strong positive relationship with crown length. Hence, long-term changes in the D(CB) of a tree were associated with long-term changes in crown length, determined by the balance between the height growth rate (ΔH) and the rising rate of the crown base (ΔH(CB)). Within the crown, ΔD's were generally greater than the rates below the crown. Even dying trees (ΔD ≈ 0 below the crown) maintained ΔD > 0 within the crown and ΔH > 0 until about 5 years before death. This growth within the crown may be related to the need to produce new leaves to compensate for leaves lost owing to the longevity of the lower crown. These results explain the different time trajectories in DBH–H relationships among individual trees, and also the long-term changes in the DBH–H relationships. The view that a rise in the crown base is strongly related to leaf turnover helps to interpret DBH–H relationships.